UPAYA MENINGKATKAN KREATIVITAS ANAK MENGGUNAKAN MEDIA POLYMER CLAY PADA SISWA KELOMPOK B DI SPS TAAM AL-MAARIJ - Ira Anggraeni; Delis Larasati (Al-Marifah | Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to improve the creativity skills of early childhood group B using polymer clay media. The type of research used is Classroom Action Research. The research model adopted follows the Classroom Action Research model by Kemmis and McTaggart, which begins with planning, action, observation, and reflection, so this reflection is used to redesign the framework for problem-solving. The subjects of this study consist of 18 individuals, specifically children in group B at SPS TAAM Al-Maarij, Kawalu District, Tasikmalaya City, totaling 17 children, comprising 6 boys and 11 girls, alongside 1 group B teacher. The object of this research is to enhance students' creativity skills through the use of polymer clay media. Data collection was conducted through observation, interviews, and documentation. At the time of the preliminary action, the percentage of children's creativity ability was 40%, which then increased in cycle I action 1 to 56.46%, in the implementation of cycle I action 2 it increased again to 68.23%, and in the implementation of cycle 2 action 1 it increased again to 74.114%, ending in cycle 2 action 2, which experienced a significant increase to 85.86%. Thus, it can be concluded that polymer clay media can enhance the creativity ability of children in group B at SPS TAAM Al-Maarij Kawalu District, Tasikmalaya City.